The value of video in work at a distance: Addition or distraction? - Matarazzo, Giacinto; Sellen, Abigail (Behaviour & Information Technology, 1999)
This paper reports on a laboratory experiment aimed at exploring the importance of person versus task space in supporting work at a distance through Multimedia Desktop Systems (MDSs). Person space refers to the ability to see and hear remote colleagues while task space refers to the ability to share work-related artifacts. A 2×2×4 mixed factorial experimental design was used (n=72) in which video quality (broad band vs narrow band) was varied for the display of remote colleagues, group size (point-to-point vs point-to-multipoint), and task. Surprisingly, subjects not only rated the poor quality video conditions more highly than good quality video conditions, but they also completed their tasks faster. These findings are explained in terms of a distraction effect imposed by the display of remote colleagues. This has practical implications for the design of MDSs.